Situating Canada’s Commercial Surrogacy Ban in a Transnational Context: A Postcolonial Feminist Call for Legalization and Public Funding - Deckha, Maneesha (McGill Law Journal / Revue de droit de McGill, 2015)
In large part due to feminist interventions in the early 1990s about the dangers of assisted reproductive technologies (ARTs) for women, Canada banned several practices related to ARTs when it enacted the Assisted Human Reproduction Act (AHRA) in 2004. Notably, the AHRA prohibited commercial surrogacy. Feminists feared that a market in surrogacy would exploit and objectify marginalized Canadian women who would be pressured into renting out their wombs to bear children for privileged couples. Since the early feminist deliberations that led to the ban, surrogacy has globalized. Canadians and other citizens of the Global North routinely travel to the Global South to source gestational surrogates. In doing so, they partake in an industry that heavily depends on material disparities and discursive ideologies of gender, class, and race. Indeed, the transnational nature of surrogacy treatment substantially reshapes the earlier feminist commodification debates informing the AHRA that took the domestic sphere as the presumed terrain of contestation. Due to the transnational North-South nature of surrogacy, a postcolonial feminist perspective should guide feminist input on whether to allow commercial surrogacy in Canada. I argue that when this framework is applied to the issue, the resulting analysis favours legalization of commercial surrogacy in Canada as well as public funding for domestic surrogacy services and ancillary ARTs.